Conceptualizing Femicide as a Human Rights Violation - Hefti, Angela (Edward Elgar Publishing, 2022)
This is an open access title available under the terms of a CC BY-NC-ND 4.0 License. It is free to read, download and share on Elgaronline.com. This thought-provoking book conceptualizes femicide as a multifaceted human rights violation and proposes state responsibility for group-related risks of violence against women and girls. In doing so, it reassesses the concept of femicide, analysing it in view of the crime of genocide, crimes against humanity, war crimes, as well as several facets of human rights.